Optical fibre wavelength filters and multiplexers - Ford, Helen D. (Cranfield University, 1994)
Polarisation-based wavelength-division multi-/demulti-plexers (WDMs) and filters have been designed, constructed and evaluated. These are compact devices made from single-mode optical fibre possessing high linear birefringence. Ihe WDMs accept two input wavelengths in a common state of polarisation, and produce orthogonally polarised outputs which are spatially separated using a polarisation-selective element. The maximum separation demonstrated is 1.5 nm, and the minimum 0.04 nm, which is two orders of magnitude better than that achieved b most other in-line WDMs. A few metres of fibre only are required. Instantaneous cross- talk values below -15 dB have been measured experimentally, and theoretical analysis of the devices predicts that values below -28 dB should be attainable. Temperature sensitivity currently limits long-term cross-talk, but also offers the possibility of tuning the centre wavelength. Methods of reducing environmental sensitivity include judicious choice of fibre type and appropriate packaging of the WDMs. These techniques are investigated and discussed. Incorporation of the WDMs in optical fibre sensing networks is demonstrated, as is separation of frequency-shifted stimulated Brillouin scattered light, generated in a fibre, from the pump frequency. Filters are constructed using concatenated sections of birefringent fibre, positioned between two polarisers. Rotation of the polarisation azimuth between sections is achieved by twistíng portions of the fibre to induce circular birefringence. Thus devices are made from a single strand of linearly birefringent fibre, less than one metre in length. Passband widths and separations are selected b changing the number of twisted sections in the filter, and altering lengths and twist angles of sections. A minimum passband width ofI0 nm has been demonstrated, at a passband separation of60 nm. Environmental stability is suíciently good for the devices to be operated as passive components.